SOVIET DIPLOMACY IN SPAIN: FROM THE PROCLAMATION OF THE SECOND REPUBLIC TO THE POPULAR FRONT - Malay Vera (Латиноамериканский исторический альманах, 2021)
Based on the analysis of published and archival materials of the WUAs of the Russian Federation (7 funds) and Western European foreign poli-cy documents, the article traces the activities of Soviet diplomacy in Spain during the Civil War of 1936-1939. The tactics of the Soviet en-voy, Consul General in Barcelona, temporary attorneys, their interac-tion with Spanish politicians, military, contradictions between Soviet representatives in Madrid and Barcelona are analyzed. The activity of professional diplomats Rosenberg M., Gaikis L., Antonov-Ovseenko V. in Spain was not always correct and tolerant in political and diplo-matic terms.